Retos de la gestión pública: presupuesto por resultados y rendición de cuentas - Franciskovic, Jubitza (2013)
Document searches draw attention to the need to discuss, theoretically and practically, the challenges that must be faced by public administration in the management of preparing a budget by results and accountability, particularly when taking into account the useful tools in the process of ensuring “good government”. To do this, a conceptual analysis of both tools was performed. Firstly, the management by results approach is presented, along with the challenges that this new framework involves for the public administration in relation to the optimisation of the use of public resources, to ensure a transparent and equitable process and to improve the performance of public bodies, becoming the basis for better accountability (the second aspect analysed in the document). Accountability becomes a challenge, on being an effective means of monitoring and sanctions between society and government, through which the public servants have to respond, explain and justify their actions, subjected to an ethical and juridical order, to the completing of objectives. It is here where the direct participation by the civil society is fundamental for the evaluation of the results. The document analyses these concepts at a time when our country has the improvement in the quality of public spending as a national priority. Thus, the results approach in the budget preparation has to be considered, by those responsible for economic policy, such as a key mechanism to achieve this, and in turn accountability is particularly linked, to the push that it attempt to give to social policy, as an important element in the administration for the management of public funds, which can help to ensure the effectiveness and transparency of these processes.